Budesonide in treatment of alcohol-induced severe hepatitis: results of randomized trial - I. I. Komkova; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2013)
Aim of investigation. To determine efficacy and safety of budesonide and prednisolone at alcoholinduced hepatitis (AH) of severe course on development of inflammation and results of the functional hepatic tests, to estimate treatment response and short-term survival rate of patients.Material and methods. Original study included 37 patients with acute AH, that have been selected from 3 medical centers and randomized in two groups. The first group included 17 patients (7 men, 10 women, mean age 46,53±11,01 years). Median of daily alcohol dose was 77 g; 25th and 75th percentiles were 55 and 96 g; duration of intake 13,41±8,55 years. Mean Maddrey index (MI) was 65,22 (37,2 to 145,4). The second group included 20 patients (16 men, 4 women, mean age was 46,5±11,89 years). A median of used alcohol consumption was 70,55 g/day (25th 75th percentiles were 37 and 88 g), duration of intake — 16,85±13,32 years. Mean MI – 58,11 (32,1 to 121,7). Groups were comparable for main clinical and laboratory features. In the first group oral budesonide 9 mg/day per os was applied, in the second – oral prednisolone 40 mg/day. Lille index was used as treatment response criterion. Following statistical criteria were used for data processing: χ2, Wilcoxon, Mann-Whitney, Kaplan – Mayer method.Results. At comparison of treatment efficacy (р=0,810) and short-term survival rate (р=0,857) no significant differences were obtained. At treatment safety analysis in the first group adverse events (AE) were registered in 23,5% of cases (in 4 of 17 patients), in the second group – in 70% (in 14 of 20 patients, р=0,011). Hepatorenal syndrome was significantly more frequent in the second group (р=0,033).Conclusions. Short-time survival in budesonide and prednisolone group does not differ significantly. At application of prednisolone frequency of AE is higher as a whole, particularly – hepatorenal syndrome.